The signing of the memorandum of understanding between UiTM Negeri Sembilan & Universitas Pahlawan Tuanku Tambusai / Sharifah Sheha Syed Aziz Baftim - Syed Aziz Baftim, Sharifah Sheha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
A Memorandum of Understanding was sealed in July 2021 between Universiti Teknologi MARA and Universitas Pahlawan Tuanku Tambusai, Indonesia, establishing friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thoughts and personnel exchange. This is the first MOU initiated by the Academy of Language Studies, UiTM Cawangan Negeri Sembilan, Kuala Pilah Campus earlier this year. Universitas Pahlawan Tuanku Tambusai is an established university that strives to strengthen its research and educational abilities and has entered into various collaborative arrangements with other universities to enhance its academic links and cooperation.